Global Trends and Research Focus on Augmented Reality for Enhancing Critical Thinking: A Bibliometric Analysis - Rahmi Lakini; Edi Istiyono; Heru Kuswanto; Aris Kurniawan; Rindang Chairunnisa (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
Learning media is a process through which learners acquire knowledge, understanding, and skills in science. Augmented Reality (AR) is a digital technology that integrates manipulable digital images into real-world environments in real time, revolutionizing dynamic learning. Research indicates that mobile-based AR learning media enhance students’ material comprehension and stimulate critical thinking. Critical thinking involves analyzing, evaluating, and logically concluding information, which is a vital skill for informed decision making. Recent studies from 2015 to 2024 highlight the rapid growth of AR research across various disciplines, including Physics Education. To analyze these studies, a bibliometric method was employed, focusing on articles published between 2015 and 2024 in the Scopus database. This analysis identified research trends related to AR’s impact on critical thinking. This study used descriptive bibliometric analysis to evaluate publications on AR and critical thinking. Results revealed a peak in publication trends in 2022 and citation trends in 2020. Taiwan led in research output. Key research areas include AR, VR, and students’ critical thinking. Emerging themes such as STEM, artificial intelligence, nursing education, and game-based learning new research directions. These findings provide a reference for future research on AR in enhancing critical thinking, with potential data sources.